ANALISIS DETERMINASI KUALITAS LAPORAN KEUANGAN DAN HUBUNGANNYA DENGAN LAKIP SKPD DI KOTA JAMBI - Arisman Arisman (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2018)
This study is to test correlation Government accounting standard, human resources, utilization of technology and accounting internal control to the quality of local government financial reports and the correlation to accountability government office performance report.(LAKIP) at local government activity unit (SKPD) in Jambi. The Research sample are head departments/ sub departments/accounting section f at local government activity unit (SKPD) in Jambi, The Research data are collected from with purposive sampling. The research Resultsf in Kendall’W showing that there’s a significant positive correlation betweent the Government accounting standart, human resources, utilization of technology and accounting internal control to the quality of local government financial reports meanwhile the reank Spearman test showing that application Government accounting standard, human resources, and accounting internal control to the quality of local government financial reports partly when the utilization of technology has no correlation to quality local government financial reports and there is no correlation between quality local government financial reports with accountability government office performance report.(LAKIP) at local government activity unit (SKPD) in Jambi Keywords : Government accounting standart Human Resources, Information Tecnology Utilization, Accounting Internal Control, And the quality of local government financial reports, accountability government office performance report.